2008
DOI: 10.4161/cbt.7.12.7069
|View full text |Cite
|
Sign up to set email alerts
|

High throughput screening of a small molecule one-bead-one-compound combinatorial library to identify attenuators of p21 as chemotherapy sensitizers

Abstract: Kidney cancer is notoriously difficult to treat when metastatic due to its resistance to conventional chemotherapy. p21 is a cyclin kinase inhibitor which, in many tumor cell lines, conveys an antiapoptotic function through its induction by the DNA damage responsive p53 pathway, such that attenuation of p21 sensitizes several disparate cancer cell lines to DNA-damaging chemotherapy. Since clinical applications with therapeutic antisense and siRNA approaches are problematic, we sought to discover other methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Since it is reported that DOX-or ETO-mediated increased p21 expression is reduced by co-treatment with Sal [14], we also tested whether Sal could reduce increased p21 levels resulting from radiation. Previously, the p21 tumor suppressor protein was shown to exert an antiapoptotic effect, thereby promoting cell survival following DNA damage [25][26][27][28][29]. We found that Sal also reduced p21 levels in radiation-treated cells, suggesting that the mechanism of Sal sensitization is conserved in nonchemotherapeutic DNA damaging drug action.…”
Section: Discussionmentioning
confidence: 71%
“…Since it is reported that DOX-or ETO-mediated increased p21 expression is reduced by co-treatment with Sal [14], we also tested whether Sal could reduce increased p21 levels resulting from radiation. Previously, the p21 tumor suppressor protein was shown to exert an antiapoptotic effect, thereby promoting cell survival following DNA damage [25][26][27][28][29]. We found that Sal also reduced p21 levels in radiation-treated cells, suggesting that the mechanism of Sal sensitization is conserved in nonchemotherapeutic DNA damaging drug action.…”
Section: Discussionmentioning
confidence: 71%
“…15 (diluted in DMSO; ref. 24) was added at a concentration of 2 μM 48 hours prior to infection; control samples were treated with DMSO alone.…”
Section: Hiv-1 Viruses and Constructs The Cxcr4-utilizing Primary Ismentioning
confidence: 99%
“…These include butyrolactone I (BL) [11], LLW10 [12], sorafenib [13] and recently reported UC2288 [14]. BL is a competitive inhibitor of ATP for binding and activation of CDK.…”
mentioning
confidence: 99%
“…We have previously discovered a small molecule p21 inhibitor, LLW10, using a one-bead one-compound combinatorial chemistry approach [12]. Rather than causing inhibition of p21 activity, LLW10 binds to p21 and induces ubiquitinization and proteosomal degradation of p21 and consequent sensitization of chemotherapy-induced apoptosis in two RCC cell lines.…”
mentioning
confidence: 99%